The Effect of Genetic Polymorphisms of Cytochrome P450 CYP2C9, CYP2C19, and CYP2D6 on Drug-Resistant Epilepsy in Turkish Children - YEŞİL, GÖZDE; Seven, Mehmet; Batar, Bahadir; Unal, Selin; Yesil, GÖZDE; Yuksel, Adnan; Guven, Mehmet (My University, 2014)
Despite the availability of several antiepileptic drugs, drug resistance remains one of the major challenges in epilepsy therapy. Genetic factors are known to play a significant role in the prognosis and treatment of epilepsy. The aim of this study was to determine the frequencies of alleles for CYP2C9, CYP2C19, and CYP2D6 genes in Turkish children with epilepsy, and to investigate the relationship between the genetic polymorphism of these genes with multiple drug resistance in epilepsy patients.